2009
DOI: 10.1111/j.1749-6632.2008.03970.x
|View full text |Cite
|
Sign up to set email alerts
|

Intrapituitary Expression and Regulation of the gp130 Cytokine Interleukin‐6 and Its Implication in Pituitary Physiology and Pathophysiology

Abstract: Interleukin (IL)-6, a member of the gp130 cytokine family, is sometimes designated as an "endocrine" cytokine because of its strong regulatory influence on hormone production. Systemically acting IL-6 derived from immune cells is a potent stimulator of the hypothalamus-pituitary-adrenal axis and therefore plays an important role in modulating immune-neuroendocrine interactions during inflammatory or infectious processes. However, IL-6 is also produced within the anterior pituitary by so-called folliculostellat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…This results in tumour expansion by concomitantly stimulating tumour cell proliferation and tumour neovascularisation (Renner et al 2009). In nude mice studies, it was found that cytokines binding to the shared gp130 subunit of the IL-6 receptor contributed to tumour progression (Graciarena et al 2004, Renner et al 2009). The authors have not identified which cytokines were responsible for the effect.…”
Section: Pituitary Carcinomamentioning
confidence: 99%
“…This results in tumour expansion by concomitantly stimulating tumour cell proliferation and tumour neovascularisation (Renner et al 2009). In nude mice studies, it was found that cytokines binding to the shared gp130 subunit of the IL-6 receptor contributed to tumour progression (Graciarena et al 2004, Renner et al 2009). The authors have not identified which cytokines were responsible for the effect.…”
Section: Pituitary Carcinomamentioning
confidence: 99%
“…IL-6 is a strong stimulant of the HPA axis and its expression is stimulated by TGF , PACAP and glucocorticoids [95,96]. At present it is Rat pituitary [73] TtT/GF cells [19] Leptin (common, ObRa and long, ObRb forms)…”
Section: Communication With the Hypothalamo-pituitary Adrenal Stress mentioning
confidence: 99%
“…These enigmatic cells constitute the major group of nonhormonal pituitary cells comprising approximately 5-10% of the anterior pituitary cell mass. With their characteristic stellate shape and long cytoplasmic processes, they form an intra-pituitary cell network coupled by gap junctions capable of transmitting intercellular signals in the gland and are associated with increased cell proliferation and hormone secretion in pituitary adenomas (Gloddek et al 1999, Renner et al 2009. In this article, Shan et al (2012) show that folliculostellate TtT-GF cells express RSUME suggesting that folliculostellate cells are exquisitely equipped to rapidly respond to local changes in oxygen concentrations to elicit RSUME-dependent production P P VEGF VEGF Figure 1 Possible RSUME-HIF1a-VEGF pathway in pituitary adenomas.…”
Section: Pituitary Tumor Hif1a-vegf Pathwaymentioning
confidence: 99%